MONITORING THE QUALITY OF TRAINING OF FUTURE SKILLED WORKERS IN BLENDED LEARNING (Innovative professional education, 2024)
In the conditions of the pandemic and martial law, blended learning in Ukraine has gained relevance and development. Accordingly, monitoring the quality of education of future qualified workers in the conditions of blended learning becomes relevant. In this work, the author provides an understanding of monitoring in professional (vocational and technical) education and its components in domestic science. He conducts atheoretical analysis of the criteria and indicators for assessing the quality of education in modern theory and practice, in particular, the criteria and indicators for assessing the quality of distance education in the conditions of blended learning.
Keywords: monitoring the quality of training, monitoring the quality of blended learning, evaluation of the quality of training, evaluation of the quality of distance training, future qualified workers, criteria and indicators of the quality of training